2019
DOI: 10.29259/jep.v17i2.8992
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local Revenue and Equalization Fund on Economic Growth in East Nusa Tenggara Province

Abstract: Fiscal decentralization is a policy made by the government to reduce fiscal dependence on the central government and create financial independence in the region. The independence of regional finance itself can be reflected through the high percentage of PAD revenue to total regional revenues. Where the existence of regional financial independence is expected to help implement regional development that can affect economic growth in the region. The purpose of this study was to determine the relationship of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
1
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
0
1
3
Order By: Relevance
“…This illustrates that the balancing funds received by an autonomous region can trigger a real increase in a region's economy. However, the results of this study are not in line with the research of Manek & Badrudin (2016), who found that balance fund does not have a significant effect on the economic growth of regencies/cities in East Nusa Tenggara Province.…”
Section: Balance Fund (Bf) On Economic Growth (Eg)contrasting
confidence: 99%
“…This illustrates that the balancing funds received by an autonomous region can trigger a real increase in a region's economy. However, the results of this study are not in line with the research of Manek & Badrudin (2016), who found that balance fund does not have a significant effect on the economic growth of regencies/cities in East Nusa Tenggara Province.…”
Section: Balance Fund (Bf) On Economic Growth (Eg)contrasting
confidence: 99%
“…Berdasarkan penelitian sebelumnya, penelitian (Aini et al, 2019), (Akhmad et al, 2019), (Sengaji et al, 2019), (Sukmaadi & Marhaeni, 2021) dan (Tuwo et al, 2021) menemukan hasil bahwa pendapatan asli daerah atau PAD berdampak positif pada pertumbuhan ekonomi regional. Serta (Diastrina, 2021) dan (Djayanthi & Juniarti, 2020) menyebutkan bahwa adanya dampak yang signifikan antara PAD dengan pertumbuhan ekonomi regional.…”
Section: Pendahuluanunclassified
“…Hasil penelitian terdahulu, diantaranya menyatakan tentang keterkaitan antara PAD dengan pertumbuhan ekonomi yang telah dikaji sebelumnya oleh (Aini, Kurnia, & Wibisono, 2019), (Sengaji, Sasongko, & Sakti, 2019), (Sukmaadi & Marhaeni, 2021), (Akhmad, 2019) dengan hasil pendapatan asli daerah atau PAD berdampak positif pada pertumbuhan ekonomi daerah. Pada teori Solow-Swan menyatakan, pertumbuhan ekonomi dapat dipengaruhi oleh sumberdaya manusia dan sumberdaya modal.…”
Section: Pengembangan Hipotesis Pengaruh Pad Terhadap Pertumbuhan Eko...unclassified
See 1 more Smart Citation